2009
DOI: 10.2478/s11696-009-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of thiophene over copper-manganese mixed oxides

Abstract: Commercial hopcalite calcined at different temperatures and hopcalite modified with noble metals (Pt, Pd, and Au) were studied in oxidation of thiophene. Surface and bulk properties of catalysts were studied using temperature-programmed reduction (TPRH2), X-ray diffraction method (XRD) and thermal analysis (TG-DTA-MS). It was shown that calcined samples displayed higher activity in comparison with commercial untreated hopcalite; however, a lower temperature of calcination was favourable. High temperature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our previous studies showed that commercial hopcalite calcined at different temperatures (300, 400, 500°C) displayed a higher activity in oxidation of thiophene in comparison with commercial untreated hopcalite [37]. Catalyst calcined at 300°C characterized by amorphous structure, the highest surface area and the best reducibility indicated the most promising performance among studied samples, however, a decrease of its activity above amorphous to crystalline phase transition was observed under reaction conditions applied.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Our previous studies showed that commercial hopcalite calcined at different temperatures (300, 400, 500°C) displayed a higher activity in oxidation of thiophene in comparison with commercial untreated hopcalite [37]. Catalyst calcined at 300°C characterized by amorphous structure, the highest surface area and the best reducibility indicated the most promising performance among studied samples, however, a decrease of its activity above amorphous to crystalline phase transition was observed under reaction conditions applied.…”
Section: Introductionmentioning
confidence: 61%
“…Moreover, the beneficial effect of an addition of Pd, Pt and Au was also observed, nevertheless noble metals doped hopcalite catalyst calcined at 400 and 500°C exhibited similar catalytic behaviour independently of calcination temperature [37][38][39]. It was also shown that commercial hopcalite modified with Pd demonstrated the highest activity among studied samples [39]. A higher activity of hopcalite containing Pd can be accompanied by better reducibility of the catalysts comparing to hopcalite modified with Pt or Au [37].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Depending on the type and amount of pollutants, the oxidation process is carried out directly in flame or thermally. The efficiency of the thermal combustion is high, almost 100% [8]. During catalytic oxidation, the oxidation of gases takes place on the surface of the catalyst.…”
Section: Oxidation Methodsmentioning
confidence: 99%